Pengaruh Bauran Pemasaran Pada Keputusan Pembelian Spontan - Era Agustina Yamini, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to examine the effect of the marketing mix (product, price, promotion, distribution) on spontaneous purchasing decisions. The sample in this study were consumers who had made a spontaneous purchase. The number of respondents in this study were 150 people. This research is a quantitative study, with the sampling method is purposive sampling. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The results of this study indicate that there is an influence between the marketing mix on impulsive buying behavior.